Activation of the Transient Receptor Potential Ion Channel TRMP8 Mediates Upregulation 0f Profibrotic Genes, A New Pathway to Tissue Fibrosis (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.
Keywords: Rheumatology; Research